Experimental investigation of quasi-static behavior of composite and fiber metal laminate panels modified by graphene nanoplatelets. (July 2021) - Fathi, Azadeh; Liaghat, Gholamhossein; Sabouri, Hadi; Chizari, Mahmoud; Hadavinia, Homayoun; Chitsaz Charandabi, Sahand
The current study investigated the influence of incorporation of graphene nanoplatelets (GNPs) on quasi-static behavior of composite and fiber metal laminate (FML) panels. The unmodified and modified composite specimens and FML panels with 2/1 configuration were fabricated using a hand lay-up method and investigated through a quasi-static punch and indentation testing. The two sets of tests were conducted with a flat-ended indenter and the loading conditions were the same for all samples, except support spans which were varied. Following experimental testing, possible damages at the punch region were closely investigated and localized and global damages were observed. The results revealed that adding 0.2 wt% GNPs improved the strength and fracture toughness of specimens by delaying the failure modes. On the contrary, GNPs made the bonding between the aluminum and composite interface to weaken.